Internal criminal protection mechanisms for children of unknown parentage - Ashraf, Abdulkareem; حسين الاء (Journal of Legal Sciences, 2023)
Although the national law was found in order to provide protection for all members of society against crime، there are some groups of society that need more protection، due to the situation in which they are from these groups. They are of unknown parentage، and in order to provide appropriate criminal protection for their situation، it must first Determine who are the owners of this category and then examine the extent of the adequacy of criminal protection provided by penal laws for this category of society from the danger of crimes affecting their lives and their physical and mental integrity..